PROFITABILITY MEMODERASI KEPEMILIKAN MANAJERIAL, LIQUIDITY, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Rania Arabella (2022)
This research is a quantitative study that aims to determine the effect of managerial ownership, liquidity, and sales growth towards financial distress, moderated by profitability, and with leverage and firm size as control variables. Financial distress as a variable in this study is measured using the modified Altman Z-Score for manufacturing companies. The samples used in this study are 107 manufacturing companies that are listed in the Indonesian Stock Ecxhange (IDX) during the period of 2018-2020. Multpile linear regression and panel data regression were used as the analysis techniques using STATA 16 with a significance level of 5%. The results of this study show that (1) managerial ownership does not have a significant effect towards financial distress. (2) liquidity does not have a significant effect towards financial distress (3) sales growth has a significant effect towards financial distress (4) profitability is not able to moderate the relationship between managerial ownership and financial distress. (5) profitability is not able to moderate the relationship between liquidity and financial distress. (5) profitability is not able to moderate the relationship between sales growth and financial distress.